Dietary intakes and risk of lymphoid and myeloid leukemia in the European Prospective Investigation into Cancer and Nutrition (EPIC). - Saberi Hosnijeh, F; Peeters, P; Romieu, I; Kelly, R; Riboli, E; Olsen, A; Tjønneland, A; Fagherazzi, G; Clavel-Chapelon, F; Dossus, L; Nieters, A; Teucher, B; et al. (2014)
The etiology of leukemias cannot entirely be explained by known risk factors, including ionizing radiation, benzene exposure, and infection with human T cell leukemia virus. A number of studies suggested that diet influences the risk of adult leukemias. However, results have been largely inconsistent. We examined the potential association between dietary factors and risk of leukemias among participants of the European Prospective Investigation into Cancer and Nutrition study. Among the 477,325 participants with mean follow-up of 11.34 yr (SD = 2.47), 773 leukemias (373 and 342 cases of lymphoid and myeloid leukemia, respectively) were identified. Diet over the previous 12 mo was assessed at baseline using a validated country-specific dietary questionnaire. Cox proportional hazards regression was used to explore the association between dietary factors that have previously been associated with leukemia risk, including red and processed meat, poultry, offal, fish, dairy products, vegetables, fruits, and seeds/nuts, and risk of both lymphoid and myeloid leukemias. No significant associations were observed between dietary measures and total, lymphoid, and myeloid leukemias. Additional subtype analyses showed no dietary association with risk of major subtypes of leukemias. In summary, this study did not support a possible link between selected dietary factors and risk of leukemias.